2021
DOI: 10.1007/s42452-021-04264-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducing enteric methane production from buffalo (Bubalus bubalis) by garlic oil supplementation in in vitro rumen fermentation system

Abstract: Enteric methane production contributes significantly to the greenhouse gas emission globally. Although, buffaloes are integral part of livestock production in Asian countries, contributing milk, meat and draft power, the contribution of enteric methane to environmental pollution attracts attention. The present study investigated the efficacy of garlic (Allium sativum) oil in reducing enteric methane production from buffaloes (Bubalus bubalis) by in vitro rumen fermentation. Garlic oil (GOL) was tested at four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Differences observed with ruminal fermentation and feed degradability may possibly explained by differences in dose, dietary composition, and controlled in vitro conditions used. In addition, the potential effect of vegetable oils supplemented to the diet on abatement of CH4 coincided with previous in vivo (Mao et al, 2010;Bayat et al, 2018;Lima et al, 2019) and in vitro (Dey et al, 2021) research findings. Diet supplemented with NSO affected net GP, feed degradability, and ruminal fermentation in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 84%
“…Differences observed with ruminal fermentation and feed degradability may possibly explained by differences in dose, dietary composition, and controlled in vitro conditions used. In addition, the potential effect of vegetable oils supplemented to the diet on abatement of CH4 coincided with previous in vivo (Mao et al, 2010;Bayat et al, 2018;Lima et al, 2019) and in vitro (Dey et al, 2021) research findings. Diet supplemented with NSO affected net GP, feed degradability, and ruminal fermentation in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 84%
“…In this experiment, acetate and propionate proportions showed a quadratic and linear response when increasing garlic inclusion, respectively ( Table 2 ). Similar to the concentration of NH 3 -N, fermentation may be affected differently according to the garlic inclusion level [ 30 ]. Additionally, the greater concentration of NH 3 -N at 2.5% of garlic inclusion could explain the greater proportion of acetate because acetogenic bacteria mainly utilize NH 3 -N as a source of nitrogen [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2021) Garlic oil 2 mL/d per sheep 122 d sheep the pregnant vivo = = Mahmoud and Salah (2017) Garlic oil 0.4, 0.8 and 1.2 63 d lambs 2.5–3 mo vivo Canbolat et al. (2021) Garlic oil 1.0, 2.5, and 5.0 μL per 30 mL of buffered rumen fluid after 24 h of incubation Murrah buffalo steers 2.5 yr vitro ↓ (2.5, 5.0) ↑ (5.0) ↓ (1.0, 2.5) ↑ (1.0) Dey et al. (2021) Garlic oil 3, 30, 300 and 3000 mg/L of rumen fluid 8 d vitro ↑ (300, 3000) ↑ (300) ↓ (30, 300, 3000) ↑ (30, 300, 3000) ↑ (30, 300, 3000) ↓ (300, 3000) Busquet et al.…”
Section: Effects Of Garlic Products On Ruminal Microbial Ecosystemsmentioning
confidence: 99%
“…Garlic powder, oil and allicin are able to reduce the methane emissions of ruminants ( Dey et al., 2021 ; Ma et al., 2016 ; Zafarian and Manafi, 2013 ). Zafarian and Manafi (2013) demonstrated that the addition of 20 g/kg of garlic powder (DM basis) into the diet for 120 d can produce a 31% reduction in methane emissions from lactating Murrah buffaloes.…”
Section: Effects Of Garlic Products On Ruminal Microbial Ecosystemsmentioning
confidence: 99%